2014
DOI: 10.1021/jf501113j
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroalkyl Acid Contamination and Polyunsaturated Fatty Acid Composition of French Freshwater and Marine Fishes

Abstract: In this study, French marine and freshwater fish perfluoroalkyl acid (PFAA) contamination are presented along with their fatty acid (FA) composition to provide further elements for a risk/benefit balance of fish consumption to be assessed. The 29 most consumed marine fish species were collected in four metropolitan French coastal areas in 2004 to constitute composite samples. Geographical differences in terms of consumed species and contamination level were taken into account. Three hundred and eighty-seven co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…As for PFOA the bioaccumulation in fish was found to be low (Falk et al, 2015;Goeritz et al, 2013;Martin et al, 2003a,b;NICNAS, 2005) and levels in humans and terrestrial wildlife were also low (in comparison to levels of long-chain PFAS), or not detectable (Bytingsvik et al, 2012;ENVIRON International Corporation, 2014;Falandysz et al, 2006;Leat et al, 2013;Loi et al, 2011;Olsen et al, 2009;Persson et al, 2013;Russell et al, 2013;Taniyasu et al, 2003Taniyasu et al, , 2013Thompson et al, 2011;Van De Vijver et al, 2005;Vicente et al, 2015;Yamada et al, 2014). Field based BCF values are indicated to be higher than those determined in the laboratory, but still below 500 (Hong et al, 2014;Kwadijk et al, 2010;Naile et al, 2013).…”
Section: Hazard Assessment Of Diffusively Emitted Dwr Related Substancesmentioning
confidence: 97%
“…As for PFOA the bioaccumulation in fish was found to be low (Falk et al, 2015;Goeritz et al, 2013;Martin et al, 2003a,b;NICNAS, 2005) and levels in humans and terrestrial wildlife were also low (in comparison to levels of long-chain PFAS), or not detectable (Bytingsvik et al, 2012;ENVIRON International Corporation, 2014;Falandysz et al, 2006;Leat et al, 2013;Loi et al, 2011;Olsen et al, 2009;Persson et al, 2013;Russell et al, 2013;Taniyasu et al, 2003Taniyasu et al, , 2013Thompson et al, 2011;Van De Vijver et al, 2005;Vicente et al, 2015;Yamada et al, 2014). Field based BCF values are indicated to be higher than those determined in the laboratory, but still below 500 (Hong et al, 2014;Kwadijk et al, 2010;Naile et al, 2013).…”
Section: Hazard Assessment Of Diffusively Emitted Dwr Related Substancesmentioning
confidence: 97%
“…Most notable among these are perfluorooctanoic acid (PFOA) and perfluorooctanesulfonate (PFOS). 6,7 It has been shown that they could cause tumor and nontumor effects on the immune and nervous systems and adversely affect hepatic function, reproduction, and development. 8−10 Besides, data of in vitro studies on human cell lines presented evidence that both PFOA and PFOS may pose toxic effects in terms of oxidative damage, membrane disruption, and interference of endogenous enzyme activity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Such findings have led to efforts to better understand the potential toxicological effects that may be inherent to these compounds. Most notable among these are perfluorooctanoic acid (PFOA) and perfluorooctanesulfonate (PFOS). , It has been shown that they could cause tumor and nontumor effects on the immune and nervous systems and adversely affect hepatic function, reproduction, and development. Besides, data of in vitro studies on human cell lines presented evidence that both PFOA and PFOS may pose toxic effects in terms of oxidative damage, membrane disruption, and interference of endogenous enzyme activity. The perfluoroalkyl chemicals are mainly distributed in serum, liver, and blood of animals living anywhere from the Polar Regions to industrialized areas because of their long half-lives in living organisms. , In addition, the rate of elimination is enhanced for short carbon chain lengths, while PFAAs with longer chains are more bioaccumulative drawing from the biomonitoring data. , Because of the hydrophobic group and the polar end in PFAAs, they have great potential to cross membranes and to enter erythrocytes . However, details on the mechanisms for PFAA-induced oxidative cytotoxicity still need to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…It was also confirmed that fish, shellfish, meat, and other products of animal origin such as giblets are major contributors of PFAAs in the human diet [137]. Studies conducted by Yamada supported the thesis that fish and seafood are highly contaminated by PFAAs [138,139]. Freshwater fish consumers were the most exposed to PFOS at a level of 7.5 ng•kg −1 •bw•day −1 , and to a lesser extent to PFUnDA, PFDA, and PFHpS (perfluoroheptanesulfonic acid), whilst seafood consumers were the most exposed to PFOA (1.2 ng•kg −1 •bw•day −1 ), followed by PFNA and PFHxS.…”
Section: Dietary Intake Of Pfaasmentioning
confidence: 91%